Kebijakan Hukum Terhadap Pelaku Tindak Pidana Pencucian Uang - Lestari Aprilia; Taufik Siregar; Rizkan Zulyadi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
The purpose of this study is to analyze legal arrangements, legal policies and countermeasures to prevent the occurrence of money laundering crimes according to Indonesian law, against money laundering criminals (Study Decision No. 630/Pid.Sus/2019/PN. Mdn). The nature of this research is analytical descriptive, by thoroughly and systematically describing legal policies against money laundering criminals using normative legal research. Law Number 8 of 2010, is a legal arrangement for the crime of money laundering, in Articles 3 and 4 it is an active money laundering crime, while in Article 5 it is passive. Legal policy against perpetrators of money laundering crimes where perpetrators must be held accountable for their actions. The panel of judges sentenced the Defendant to imprisonment for 5 (five) years and a fine of Rp. 1,000,000,000.00 (one billion rupiah) provided that if the fine was not paid, it was replaced with imprisonment for 3 (three) months. In order to prevent and eradicate money laundering, including various criminal acts that produce illegal assets, a Financial Transaction Reports and Analysis Center (PPATK) has been established whose main task is to assist law enforcement in preventing and eradicating money laundering and serious crimes. others by providing intelligent information.